DISTRIBUTION AND POPULATION DENSITIES OF PLANT-PARASITIC NEMATODES ASSOCIATED WITH GINGER (ZINGIBER OFFICINALE) IN KADUNA STATE, NIGERIA - Bulus, Julius; Abraham, Peter; Joshua, Mercy; Shamaki, Dauda Elisha; Okolo, Christopher Tobe; Chindo, Paul Sule (FUDMA JOURNAL OF SCIENCES, 2020)
Ginger (Zingiber officinale) is an important cash crop in Nigeria. In spite of the economic importance of plant-parasitic nematodes reported on ginger, little or no information is available as regards plant-parasitic nematodes diversity and abundance on ginger in Nigeria. This work was conducted in 2018 to identify plant-parasitic nematodes associated with ginger in Kaduna state and to determine their population densities. Three Local Government Areas (LGA) were visited and between 12 to 16 ginger farms were sampled per LGA. A total of 42 soil samples was collected at a depth of 0 - 30 cm of the plant rhizosphere. Plant-parasitic nematodes were extracted from the soil using modified sieving and decanting method. Identification to genera level was done using identification keys viewing with dissecting microscope at X40 magnification. Nineteen (19) genera of plant-parasitic nematodes were identified, with 12 genera occurring in all LGA(s). Scutellonema (113.33), Meloidogyne (110), and Pratylenchus (93.33) were the most abundant per 100 ml of soil when locations are combined. Plant-parasitic nematodes population average was 870-950 per 100 ml of soil. All locations showed a high percentage similarity of plant-parasitic nematodes diversity and were statistically similar. This high diversity and population abundance can be among the reasons for the low productivity of ginger in Nigeria. It is therefore important to educate farmers on the economic importance of plant-parasitic nematodes on ginger and its management. Further research using the most occurring genera to establish the threshold population densities capable of causing economic yield loss needs to be conducted